"Secondary supervision" in Canada: a qualitative examination of how probationers' loved ones understand community supervision - Maier, Katharina (Punishment, probation and parole, 2024)
In the current chapter, we examine the nature, distribution and experiences of probation in Canada. More specifically, drawing upon in-depth interviews with probationer loved ones, we examine the experiences of what we refer to as secondary supervision. The concept captures how individuals with a loved one (i.e. family member or partner) on probation understand, make sense of and feel affected by their loved one’s probation order. Complementing existing literature on the collateral consequences of incarceration or ‘secondary prisonization’, we show how secondary supervision burdens probationer loved ones mentally and emotionally as they must navigate the uncertainties of their loved one’s legally precarious status. We highlight the necessity of expanding probation research and of our thinking about ‘mass supervision’ to consider the collateral and unintended consequences of community-based supervision.